Fostering inclusive welfare and Islamic financing through Islamic social finance digitalization strategy - Syarifuddin, Ferry (Edelweiss Applied Science and Technology, 2024)
Islamic Social Finance (ISF) is one solution for poverty alleviation, which is a major concern in developing countries like Indonesia. However, the performance of ISF in Indonesia, both in terms of collection and management, is still far from expectations. To address this problem, a digital transformation of ISF is needed by leveraging technologies that come with both advantages and disadvantages. This study employs a Delphi ANP-BOCR analysis to determine the most optimal technology for ISF digitalization, which result is supported by meta-analysis findings. The result shows that cloud computing is the most optimal technology when only benefits and costs are evaluated. When all factors, including benefits, opportunities, costs, and risks, are considered, digital platform proves to be the most optimal technology for both the short and long term. BOCR analysis also confirms that digital platform and cloud computing are the most optimal technology. Meta-analysis further supports the contribution of digital platform in improving social finance performance. To optimize the implementation of ISF digitalization in Indonesia, this study provides an alternative model that incorporates multiple technologies.